Factors associated with dropout in a lifestyle modification program for weight management in children and adolescents. Issue 6 (November 2020) - Park, Jane; Woo, Sarah; Ju, Young-Su; Seo, Young-Gyun; Lim, Hyun-Jung; Kim, Yoon-Myung; Noh, Hye-Mi; Lee, Hye-Ja; Park, Sang Ick; Park, Kyung Hee
Highlights: Different factors were associated with short- and long-term dropout. Dropout rates in obesity intervention are associated with family factors. Focus on early-stage factors may reduce dropout rates in obesity intervention. Abstract: Background: Significant dropout rates remain a serious concern in pediatric weight control program, but few studies have identified predictors of dropout. Aims: The objective of the study is to identify factors associated with dropout from a pediatric lifestyle modification weight control program at different phases. Methods: Data on overweight and obese participants ( n = 242) aged 11–18 years in the Intervention for Childhood and Adolescent Obesity via Activity and Nutrition (ICAAN) study were collected at baseline, 6-months, and 24-months through self-report and a laboratory test. Logistic regression analysis was performed for those who dropped out during the first 6-months, and multivariate generalized estimating equation analysis identified longitudinal factors associated with those who dropped out after 24 months. Results: Lower family functioning (OR = 2.30, 95% CI [1.18−4.46]), exercise group (OR = 0.36, 95% CI [0.15−0.86]), lower initial attendance rate (OR = 6.09, 95% CI [2.94−12.6]), and non-self -referral pathways (OR = 2.35, 95% CI [1.05−5.27]) were significantly associated with 6-month dropouts. For late dropout, lower family functioning (OR = 1.71, 95% CI [1.06−2.77]) and lower initial attendance rates (OR = 2.06, 95% CI [1.12−3.81]) remained significant. Conclusion: Family function and initial attendance rate were associated with lower dropout rates. Developing a supportive family environment and focusing on the early-stage factors at the intervention's outset may reduce overall dropout rates in obesity prevention intervention.